N-Nitroso Group-Assisted Nucleophilic Aromatic Substitution of 6-Chloropyrimidines: A Facile and Efficient Synthesis of Pyrimidine-4,6- and -2,4-diamines - Jakubkiene, Virginija; Zurba, Justinas; Cikotiene, Inga (Synthesis, 2013)
An N-nitroso group was used to activate chloropyrimidines toward nucleophilic substitution by amines. This permitted a simple, one-pot, high-yielding synthesis of pyrimidine-4,6- and -2,4-diamines.
Keywords: heterocycles; pyrimidines; nucleophilic aromatic substitutions; amines